2017
DOI: 10.12693/aphyspola.131.527
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of LYSO Crystal for the TAC-PF Electromagnetic Calorimeter

Abstract: In addition to PWO and CsI(Tl) crystals, cerium doped LYSO crystal is considered for the electromagnetic calorimeter part of the Turkish Accelerator Center Particle Factory (TAC-PF) detector, because of its high light yield, fast decay time and good radiation hardness. In this work, LYSO crystals arranged in 3×3 and 5×5 matrices have been simulated against photons in the energy range between 50 MeV and 2 GeV, using Geant4 simulation code. Energy resolutions have been estimated considering the contribution of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The previous studies with CsI(Tl), PWO, and LYSO crystals showed that the mentioned simulation procedure gives compatible and reasonable results compared to experimental results [16,17]. It was shown that number of average photoelectrons determined at the end of whole process is reasonable if considering it with experimental ones and energy resolution values obtained are in agreement.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…The previous studies with CsI(Tl), PWO, and LYSO crystals showed that the mentioned simulation procedure gives compatible and reasonable results compared to experimental results [16,17]. It was shown that number of average photoelectrons determined at the end of whole process is reasonable if considering it with experimental ones and energy resolution values obtained are in agreement.…”
Section: Methodssupporting
confidence: 58%
“…It is seen that the resolutions increase with back face areas and calorimeter thicknesses. It can be stated that the resolutions belonging to the geometries of 25 mm x 25 mm beam facing area and calorimeter thicknesses of 25 cm or 27 cm gives more compatible results with previous studies [16,17]. Therefore, energy resolution functions were parametrized with these detector geometries.…”
Section: Resultsmentioning
confidence: 77%
“…Due to all of the above-mentioned properties, this crystal has also attracted the attention of experimental high energy physics research groups working to improve the performance of electromagnetic calorimeters, such as the proposed SuperB forward parts of the endcap calorimeter [7], the KLOE experiment [8], the COMET experiment at J-PARC [9], and the Muon-to-Electron (Mu2e) experiment [10]. In addition to lead tungstate (PWO) and Thallium-activated Cesium Iodide (CsI(Tl)) crystals, LYSO scintillation crystals may also be studied for the electromagnetic calorimeter (ECAL) section of the proposed Turkish Accelerator Center-Particle Factory (TAC-PF) detector [11]. This paper reports the results of a simulation study carried out with Geant4 to evaluate the position resolution of LYSO scintillation crystals for incident electrons at an energy range from 0.1 GeV to 2 GeV.…”
Section: Introductionmentioning
confidence: 99%
“…Due to all of the above-mentioned properties, this crystal has also attracted the attention of experimental high energy physics research groups working to improve the performance of electromagnetic calorimeters, such as the proposed SuperB forward parts of the endcap calorimeter [7], the KLOE experiment [8], the COMET experiment at J-PARC [9], and the Muon-to-Electron (Mu2e) experiment [10]. In addition to the lead tungstate (PWO) and Thallium activated Cesium Iodide (CsI(Tl)) crystals, the LYSO scintillation crystals may also be studied for the electromagnetic calorimeter (ECAL) section of the proposed Turkish Accelerator Center-Particle Factory (TAC-PF) detector [11]. This paper reports the results of a simulation study carried out with Geant4 to evaluate the position resolution of the LYSO scintillation crystals for incident electrons at an energy range from 0.1 GeV to 2 GeV.…”
Section: Introductionmentioning
confidence: 99%